Effect of immediate dentine sealing on the fracture strength of lithium disilicate and multiphase resin composite inlay restorations. (August 2017) - van den Breemer, Carline R.G.; Özcan, Mutlu; Cune, Marco S.; van der Giezen, Rianne; Kerdijk, Wouter; Gresnigt, Marco M.M.
Abstract: Purpose: Limited information is available on the effect of Immediate Dentin Sealing (IDS) on the fracture strength of indirect partial posterior restorations. This study evaluated the effect of IDS on the fracture strength and failure types of two indirect restorative materials. Materials and methods: Standard MOD inlay preparations were made on sound molars (N=40, n=10 per group) and randomly divided into four groups to receive the inlay materials with and without the application of IDS: Group L-IDS-: Li2 Si2 O5 (Lithium disilicate, IPS e.max) without IDS; Group L-IDS+: Li2 Si2 O5 with IDS; Group MR-IDS-: Multiphase resin composite (MR, Lava Ultimate) without IDS; MR-IDS+: MR with IDS. Inlays made of L were etched with 5% hydrofluoric acid, and MR inlays were silica coated. After silanization, they were cemented using adhesive resin cement (Variolink Esthetic DC). The specimens were thermo-mechanically aged (1.2×10 6 cycles, 1.7 Hz, 8000 cycles, 5–55 °C) and then subjected to load to failure (1 mm/min). Failure types and locations of debondings were classified. Data were statistically analyzed using ANOVA, Mann Whitney U-test and Chi-square tests (α=0.05). Two-parameter Weibull distribution values including the Weibull modulus, scale (m) and shape (0), values were calculated. Results: After aging conditions, no apparent changes were observed in marginal integrity but occlusal wear facets were more common with MR than with L (p<0.001). Material type and the application of IDS significantly affected the results (p=0.013). While group L-IDS- showed the lowest mean fracture strength (1358±506 N) among all groups (p<0.05), application of IDS significantly increased the results significantly (L-IDS+: 2035±403 N) (p=0.006). MR groups with and without IDS, did not show significant difference (MR-IDS-: 1861±423, MR-IDS+: 1702±596 N) (p=0.498). When materials without IDS are compared, L showed significantly lower results than that of MR (p=0.035). With the application of IDS, no significant difference was noted between L and MR materials (p=0.160). Weibull distribution presented the highest shape (0) for L-IDS+ (5.66) compared to those of other groups (3.01–4.76). Neither the material type (p=0.830), nor the application of IDS (p=0.54) affected the severity of the failure types. In 95% of the cases, the IDS layer left adhered on the tooth surface after fracture tests. In groups where no IDS was used, resin cement remained on the tooth surface in 44% of the cases (p=0.001). No significant differences were observed between the materials with respect to cement remnants or IDS after fracture (p=0.880). The incidence of repairable failure types (83%) was more common with L than with MR (75%) material (p>0.05). Conclusion: Immediate dentin sealing improves adhesion, and thereby the fracture strength of inlays made of lithium disilicate but not that multiphase resin composite.